Effective utilization of waste plastic oil in a direct injection diesel engine using high carbon alcohols as oxygenated additives for cleaner emissions. (15th June 2018) - Damodharan, D.; Sathiyagnanam, A.P.; Rana, D.; Saravanan, S.; Rajesh Kumar, B.; Sethuramasamyraja, B.
Graphical abstract: Highlights: A blend of recycled fuel and biofuel was used to power diesel engine. Best method for utilizing WPO in diesel engine with low smoke. Best among pentanol, hexanol and octanol for blending with WPO was determined. Alcohol/WPO blends delivered better fuel consumption and low smoke. Abstract: Waste plastic in municipal solid wastes degrade very slowly over several years and poses a serious challenge for sustainable environment. Hydrocarbons embodied in waste plastic could be converted into liquid fuel. Recycling waste plastic oil (WPO) in diesel engines offers a sustainable solution for ecological safety and energy security. However WPO produces carcinogenic smoke emissions in diesel engines that have to be controlled. This study attempts to minimize these emissions with the aid of oxygenated three high-carbon alcohols and also provides a comparative analysis on the effects of their addition to WPO individually on emissions and performance of a single cylinder diesel engine. A response surface methodology (RSM) based optimization using a 3-factor × 3-level full factorial experimental design was employed to find the optimum combination of exhaust gas recirculation (EGR), injection timing and alcohol with an objective to minimize NOx and smoke emissions with minimum BSFC. Three injection timings (21°, 23° and 25°CA bTDC) and three EGR rates (10, 20 and 30%) were used. Multiple regression models developed using RSM for NOx, smoke density and BSFC were found to be statistically significant. Interactive effects between injection timing and EGR on responses for all blends were compared. From desirability approach, WPO70P30 injected at 21° CA bTDC with 10% EGR delivered optimum emission and performance characteristics with a maximum desirability of 0.968. Pentanol was found to be the best among n-hexanol and n-octanol for this purpose. Confirmatory tests validated the models to be adequate with an error in prediction within 6%. With reference to diesel, n-pentanol with WPO injected at 21° CA bTDC with 10% EGR reduced smoke emissions by 76.8% and increased NOx emissions by 32% with an improvement in BSFC by 17.8%. With respect to neat WPO, the same blend reduced smoke emissions by 74.2% and increased NOx emissions by 9.7% with an improvement in BSFC by 3.2%.